Lucky - Stapley, Marissa (Simon & Schuster Canada, 2021)
When talented grifter Lucky Armstrong discovers that a lottery ticket she bought on a whim is worth millions, she must find a way to cash in the winning ticket without the police arresting her for her past crimes.